2021
DOI: 10.1002/jcp.30574
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid PTEN deficiency aggravates renal inflammation and fibrosis in angiotensin II‐induced hypertension

Abstract: Hypertension is a major cause of chronic kidney disease. However, the pathogenesis of hypertensive kidney disease is not fully understood. Recently, we have shown that CXCL16/phosphoinositide-3 kinase γ (PI3Kγ) plays an important role in the development of renal inflammation and fibrosis in angiotensin II (AngII) induced hypertensive nephropathy. In the present study, we examined the role of phosphatase and tensin homolog (PTEN), a major regulator of PI3K signaling, in the pathogenesis of renal inflammation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Recent studies have indicated that bone-marrow-derived fibroblasts, termed fibrocytes, make an important contribution to the populations of activated fibroblasts and have a crucial role in renal fibrosis development [4][5][6][7][8][9]. Bone-marrow-derived fibroblasts share the characteristics of fibroblasts, such as the expression of collagen I, platelet-derived growth factor receptor-β (PDGFR-β), and vimentin, as well as the characteristics of hematopoietic cells, such as the expression of CD45 and CD11b [10,11]. Our previous studies have demonstrated that these cells contribute significantly to the pathogenesis of renal fibrosis [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that bone-marrow-derived fibroblasts, termed fibrocytes, make an important contribution to the populations of activated fibroblasts and have a crucial role in renal fibrosis development [4][5][6][7][8][9]. Bone-marrow-derived fibroblasts share the characteristics of fibroblasts, such as the expression of collagen I, platelet-derived growth factor receptor-β (PDGFR-β), and vimentin, as well as the characteristics of hematopoietic cells, such as the expression of CD45 and CD11b [10,11]. Our previous studies have demonstrated that these cells contribute significantly to the pathogenesis of renal fibrosis [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…After obtaining the FLNC, the cluster module of isoseq3 is further used to cluster FLNC reads using hierarchical n*log(n) alignment and iterative cluster merging. In the novel variant isoform (NVI) calling step following pre-processing step described above, we utilized the collapse_isoforms_by_sam.py of cDNAcupcake [17], which takes bam file as input obtained by mapping cluster.fasta files to the pre-defined reference using minimap2 [18], to collapse two or more identical transcript isoforms into a unique transcript isoform. [Fig2A] Simultaneously, the number of full-length reads corresponding to different unique isoforms was also obtained, which are important supporting evidence for the called isoforms, and will be used as the parameter in the following filter step.…”
Section: Pipeline Overviewmentioning
confidence: 99%
“…Based on this principle, neoantigen-based immunotherapy has been developed by pharmaceutical companies or research institutions as a promising cancer treatment [4][5][6]. Additionally, novel proteins are also associated with other complex diseases, for instance, Alzheimer's [7], type II diabetes [8], liver disease [9][10][11][12][13][14], kidney disease [15][16][17][18][19][20], Obesity [21][22][23][24][25], and cardiovascular disease [26]. Therefore, effective identification of novel proteins is imperative for understanding human diseases and developing corresponding therapies.…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that the lncRNA TapSAKI promotes the expression of phosphatase and tensin homolog (PTEN), TLR4/NF-κB pathway–related proteins TLR4 and P-p65, and apoptotic protein cleaved caspase-3 through negative regulation of miR-22 in renal injury induced by urinary sepsis. The miR-22/PTEN/TLR4/NF-κB pathway promotes the inflammatory injury of HK-2 cells and myeloid PTEN deficiency aggravates renal inflammation and fibrosis ( Shen et al, 2019 ; An et al, 2022 ). Another lncRNA, HOXA cluster antisense RNA 2, showed a protective effect in sepsis-induced AKI by targeting miR-106B-5p and blocking the Wnt/β-catenin and NF-κB pathways ( Wu et al, 2020 ).…”
Section: Lncrna and Akimentioning
confidence: 99%